2011
DOI: 10.1016/j.jds.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral mandibular odontogenic fibroma (WHO type): Report of a case with 5-year radiographic follow-up

Abstract: Odontogenic fibromas are a rare benign odontogenic neoplasia, characterized by the presence of odontogenic epithelium with an inactive appearance in a cellular fibrous stroma. Histopathologically there are two types of odontogenic fibromas: an epithelium-poor type (simple type) and an epithelium-rich type (WHO or complex type). Depending on its primary location, two variables can be distinguished, one central or intraosseous and one peripheral or extraosseous. Several cases were published in the literature, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Half of the cases present posterior to the first molar and up to one-third accompany an unerupted third molar [10]. 12% of COF exhibit radiopaque flecks scattered within the lesion [24]. Radiographic features are not pathognomic.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Half of the cases present posterior to the first molar and up to one-third accompany an unerupted third molar [10]. 12% of COF exhibit radiopaque flecks scattered within the lesion [24]. Radiographic features are not pathognomic.…”
Section: Discussionmentioning
confidence: 99%
“…In Contrast to dental follicle, COF is a destructive lesion with persistent growth. Only 1 out of 57 of COF examined by Ramer et al, has reported to have features of dentigerous cyst [24]. Reviewing the literature, COF can have the following subtypes:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations